Human urinary GM2-activator protein as a potential biomarker for lung cancer - Potprommanee L. (2014)
Human urine can be obtained from most patients by noninvasive ways of collection. It is a rich source of biomarkers for diagnostic tests, therapeutic guidance and prognostic information for patients and clinicians. Recently, the protein expression pattern of urine samples from lung cancer patients and healthy controls were compared using two-dimensional gel electrophoresis (2-DE). GM2 activator protein (GM2AP) in lung cancer patients with 2.5-4.0 folds higher than that found in healthy controls was the protein of interest, and this protein was focused because it is related to tumor-associated gangliosides found in cancer progression. The aim of this study was to investigate the urinary biomarkers associated with lung cancer. First, we applied proteomic approach to confirm the increase level of GM2AP in urine samples from lung cancer patients and healthy controls. Then, the expression level of urinary GM2AP was quantified using Western blotting and Enzyme-Linked Immunosorbent Assay (ELISA). The results show that the expression level of GM2AP significantly increased in each subtype of lung cancer patients (P<0.05). In addition, nano liquid chromatography coupled online with tandem mass spectrometry (NanoLC-MS/ MS) provided evidence of an increase of GM2AP with the glycan structure identification from doublely charge at m/z 1202.1025 corresponding to the structure of (Hex)3(HexNAc)2(Fuc)1 linked with peptide (PIIVOGNVTLSVVG). Overall data suggested that the GM2AP may be associated with lung cancer and may be useful as a marker to monitor lung cancer prognosis. © 2013 Potprommanee L, et al.